PENGARUH PENGAPLIKASIAN PHOTOSYNTHETIC BACTERIA TERHADAP PERTUMBUHAN BIBIT KOPI ROBUSTA (Coffea canephora) DI MEDIA TANAH ULTISOL - juliyanti, juliyanti; Setiawan, Beny; Kurniawan, Tardi; Fitry Ramanda, Rika (Politeknik Negeri Ketapang, 2024)
Coffee is one of the mainstay commodities in the Indonesian plantation sector. To encourage plant growth and improve the quality of coffee plants, Photosynthetic Bacteria (PSB) are applied, which are autotrophic bacteria that can photosynthesize. Providing PSB to the soil can help increase soil fertility, accelerate plant growth, physiologically active compounds and polysaccharides. The purpose of this study was to determine the effect and best concentration of Photosynthetic Bacteria (PSB) on the growth of robusta coffee plants (Coffea canephora) in Ultisol soil. This study used a non-factorial Completely Randomized Design (CRD), consisting of 5 treatments and 5 replications so that there were 25 experimental units, where each experimental unit consisted of 3 seed samples so that the total number was 75 seed samples. The treatments were P0: soil media without PSB, P1: Concentration 25 ml/L P2: Concentration 50 ml/L, P3: Concentration 75 ml/L, P4: Concentration 100 ml/L. The data obtained were analyzed statistically using Analysis of Variances (ANOVA). If there is a significant effect, it will be continued with Duncan's Multiple Range Test (DMRT) at the 5% level. The results showed that the provision of Photosynthetic Bacteria (PSB) had a significant effect in increasing the growth of robusta coffee plants (Coffea canephora) in ultisol soil media on soil pH parameters, plant height, stem diameter, number of leaves, root length, and dry weight of plants. The best concentration of Photosynthetic Bacteria (PSB) administration on the growth of robusta coffee plants (Coffea canephora) aged 12 MST in the P2 treatment was a concentration of 50 ml/L with a soil pH of 6.02, plant height of 12.88 cm, stem diameter of 1.41 mm, number of leaves 6 strands, root length 12.07 cm and dry weight 0.35 g.